Creative Leadership and Work Team Activation in Economic Institutions: A Conceptual Framework for the Algerian Water Company ADE (Journal of Informatics Education and Research, 2026)
Economic institutions in Algeria face mounting pressures to enhance employee motivation and team performance in competitive markets. This conceptual article examines the impact of creative leadership on work team activation within the Algerian Water Company, a major public economic institution. Drawing on international and Algerian management literature, the study defines creative leadership as a multidimensional construct encompassing visionary thinking, intellectual stimulation, risk tolerance, and empowerment behaviors that encourage innovative problem-solving. The article develops a conceptual framework linking creative leadership dimensions to team activation mechanisms, including enhanced motivation, psychological empowerment, collective efficacy, and innovative climate. Through systematic synthesis of existing research, the framework proposes that creative leadership positively influences team outcomes such as collaborative behavior, creative performance, and organizational commitment. The study offers practical implications for leadership development in Algerian economic institutions and identifies avenues for future empirical investigation. By anchoring the discussion in water utility management context, this article contributes to understanding how creative leadership practices can address unique challenges facing Algerian public sector organizations striving for service delivery excellence and sustainability.